Compound-specific radiocarbon reveals sources and land–sea transport of polycyclic aromatic hydrocarbons in an urban estuary. (15th June 2021) - Ya, Miaolei; Wu, Yuling; Xu, Li; Li, Yongyu; Chen, Hanzhe; Wang, Xinhong
Highlights: Source appointment of PAHs based on compound specific 14 C variations was presented. Different contributions of fossil fuel and biomass to PAH species were found. River input, atmospheric deposition, and coastal currents control the Δ 14 C of PAHs. Fluvial erosions and urban oil spills affect the Δ 14 C of perylene in the estuary. Estuarine inputs and coastal currents affect the Δ 14 C of perylene on the coasts. Abstract: As typical chemical indicators of the Anthropocene, polycyclic aromatic hydrocarbons (PAHs) and their environmental behavior in urban estuaries can reveal the influence of anthropogenic activities on coastal zones worldwide. In contrast to conventional approaches based on concentration datasets, we provide a compound-specific radiocarbon ( 14 C) perspective to quantitatively evaluate the sources and land‒sea transport of PAHs in an estuarine‒coastal surficial sedimentary system impacted by anthropogenic activities and coastal currents. Compound-specific 14 C of PAHs and their 14 C end-member mixing models showed that 67−73% of fluoranthene and pyrene and 76−80% of five- and six-ring PAHs in the Jiulong River Estuary (JRE, China) originated from fossil fuels (e.g., coal, oil spill, and petroleum-related emissions). In the adjacent Western Taiwan Strait (WTS), the contributions of fossil fuel to these PAH groups were higher at 74−79% and 84−87%, respectively. Furthermore, as a significant biomarker for source allocation of terrigenous organic matter, perylene, a typical five-ring PAH, and its land‒sea transport from the basin through the JRE and finally to the WTS was quantitatively evaluated based on the 14 C transport models. In the JRE, fluvial erosions and anthropogenic emissions affected the 14 C signature of perylene (Δ 14 Cperylene, -535 ± 5‰) with contributions of > 38% and < 62%, respectively. From the JRE to the WTS, the decreased Δ 14 Cperylene (-735 ± 4‰) could be attributed to the long‒range transport of "ocean current-driven" perylene (-919 ± 53‰) with a contribution of 53 ± 8%. This compound-specific 14 C approach and PAH transport model help provide a valuable reference for accurately quantifying land‒sea transport and burial of organic pollutants in estuarine‒coastal sedimentary systems. Graphical abstract: Image, graphical abstract